ANCIENT WINDOW PANE OYSTER BED IN GOA WITH COMPARATIVE NOTES ON THE OYSTER IN AN EXTANT BED - Thomas, P A; Thanapathi, V (Indian Journal of Fisheries, 2011)
A bsd consisting of a liTge quantity of semifossdlised shells of window paneoyster Placenta placenta (Linn.) was discove,red accidently in a paddy field by theside of the river Mandovi '.n Goa. Subsequent investigations lead to the conclusionthat there was a flourishing population of window pane oyster in this rrea priorto the 16th century, and that this rich population perished subsequently as a resultof indiscriminate intervention by way of reclamation. This population is comparedwith that which exiists ft present in the Zuari estuary of Goa. Attempts are alsom de to compare the incidence and distribution of .boring sponges among thewindow pane oyster, both ancient and extant.